2020
DOI: 10.1371/journal.pone.0235273
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and septic shock after craniotomy: Predicting a significant patient safety and quality outcome measure

Abstract: Objectives Sepsis and septic shock are important quality and patient safety metrics. This study examines incidence of Sepsis and/or septic shock (S/SS) after craniotomy for tumor resection, one of the most common neurosurgical operations. Methods Multicenter, prospectively collected data from the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) database was used to identify patients undergoing craniotomy for tumor (CPT 61510, 61521,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…In their study, the incidence of sepsis in patients undergoing craniotomy was 1.21%. Zhang et al, also using the ACS NSQIP database, reported a 1.35% incidence of sepsis in patients undergoing craniotomy for tumor resection ( 20 ). Compared with the incidence of sepsis in the above two studies, the incidence of sepsis in our study was much higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the incidence of sepsis in patients undergoing craniotomy was 1.21%. Zhang et al, also using the ACS NSQIP database, reported a 1.35% incidence of sepsis in patients undergoing craniotomy for tumor resection ( 20 ). Compared with the incidence of sepsis in the above two studies, the incidence of sepsis in our study was much higher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of their patients underwent spine procedures, while patients undergoing cranial procedures only accounted for 22.2% of the population. Zhang et al, reported the incidence of sepsis in patients who underwent craniotomy for tumor resection, but not in patients who underwent craniotomy for other reasons ( 20 ). Therefore, the results of both studies could not reflect the overall epidemiological characteristics of sepsis after neurosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…The data studied obtained from the ACS NSQIP database originally uploaded by Jingwen Zhang et al. ( 13 ) (data from “Sepsis and septic shock after craniotomy: Predicting a significant patient safety and quality outcome measure”; DOI: ). The original study was an open-access article distributed under a Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The 30-day mortality was defined as mortality after discharge for the first 30 postoperative days ( 13 ).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation